Evaluation of media for determining hemolytic activity and that of API Listeria system for identifying strains of Listeria monocytogenes. - Fujisawa, T (1994)
Several media were used to evaluate the hemolytic activity of Listeria monocytogenes, and this property was used along with the API Listeria system to identify Listeria spp. All L. monocytogenes strains were identified correctly with this system, and blood agar base no. 2 and Columbia blood agar base supplemented with horse blood were suitable for detection of hemolytic activity.